Preliminary Checklist, Distribution and Host Plants of Family Aphididae (Insecta: Hemiptera) from Azad Jammu and Kashmir, Pakistan - Amin, Muhammad; Mahmood, Khalid; Qasim, Muhammad; Asghar Hassan, Muhammad; Mahmood Sarwar, Zahid; Ullah Rustam, Zafar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The northern areas of Pakistan, located at the junction of the Oriental and Palaearctic regions, are expected to harbor a rich diversity of flora and fauna. Azad Jammu & Kashmir, situated at the junction of these two regions with multiple climatic zones, extensive forest types, and rich plant diversity, remains underexplored in terms of aphid fauna. This study, based on comprehensive field surveys conducted in the Poonch division from 2015 to 2016, identified 69 aphid species in 39 genera and 10 tribes under seven subfamilies. These aphid species were associated with 71 host plant species under 59 genera and 39 families. The study also provided the first preliminary checklist of aphids in Azad Jammu & Kashmir, documenting their distribution and associated host plants.